Effect of Service Quality and Use of E-Service Technology on Customer Loyalty: A Case Study of Maxim in Aceh - Marlizar, Marlizar; Agustina, Wulan; Bachtiar, Fandy; Mukhsinuddin, Mukhsinuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the effect of service quality and use of e-service technology on customer satisfaction and customer loyalty of Maxim online transportation in Aceh. The study used Purba formula to select 96 respondents of total Maxim customers. The sampling technique used two-stage sampling, which was to determine districts/cities purposively and the city of Banda Aceh was obtained because the maxim was only in this city in the Aceh province. Furthermore, random sampling was used to determined respondents in the city of Banda Aceh. Data were obtained through questionnaires and path analysis using IBM SPSS v22 software. Data were obtained through questionnaires and analyzed using path analysis with software SPSS v22. The results reveal that customer satisfaction significantly and positively influence customer loyalty. Further, there is a significant influence on the causal relationship of service quality and the use of e-service technology on loyalty through customer satisfaction. This indicates that to boost customer loyalty, it is important to pay attention to service quality that can improve customer satisfaction.